Linguistic Intelligence in Specialist (Foreign) Language Didactics – Some Remarks on Current E-Learning Systems - Szerszeń, Paweł (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
The rapid development of electronic media has led to the development of “closed” and “open” e-learning solutions using new communication technologies or advanced language analysis systems. The purpose of this paper is to try to answer the question of what currently constitutes the so-called “linguistic intelligence” of modern glottodidactic learning systems, with special emphasis on systems for specialist (foreign) language didactics. In the paper the adaptivity (on the micro- and macroscale) and examples of micro- and macro-adaptive language didactic systems are approximated. Due to the complexity of the analysis of linguistic data, among other things, these systems can be classified as “intelligent” tools.